Listeria monocytogenes impairs enzymes of the phosphotransfer network and alters antioxidant/oxidant status in cattle brain structures - Jaguezeski A.M.* (2018)
© 2018 Elsevier Ltd Several evidences have suggested the involvement of enzymes belonging to the phosphotransfer network, formed by creatine kinase (CK), pyruvate kinase (PK) and adenylate kinase (AK), as well the oxidative stress on the pathogenesis of infectious diseases associated with the central nervous system (CNS). Thus, the aim of this study was to evaluate whether listeriosis alters the brain energy metabolism and/or causes oxidative stress in different brain structures of cattle experimentally infected by Listeria monocytogenes. The cytosolic CK activity was inhibited in the cerebral cortex, cerebellum, brainstem and hippocampus of infected animals compared to uninfected animals, while the mitochondrial CK activity was increased. The PK activity was inhibited in all brain structures of infected animals, while the AK activity was unchanged. Na + , K + -ATPase activity decreased in the cerebral cortex, cerebellum and hippocampus of animals infected by L. monocytogenes. Regarding the oxidative strees variables, the cerebellum and brainstem of infected animals showed increased thiobarbituric acid reactive substances, while the catalase activity was inhibited. Glutathione S-transferarase was inhibited in the cerebral cortex and brainstem of infected animals, and it was increased in the cerebellum. L. monocytogenes was quantified in the liver (n = 5/5) and cerebral cortex (n = 4/5) of the infected cattle. Based on these evidences, the nucleocytoplasmic communication between CK isoenzymes was insufficient to avoid an impairment of cerebral bioenergetics. Moreover, the inhibition on brain PK activity caused an impairment in the communication between sites of ATP generation and ATP utilization. The lipid peroxidation and alteration on antioxidant status observed in some brain structures were also involved during the disease. In summary, these alterations contribute to disease pathogenesis linked to CNS during cattle listeriosis.